PENGARUH KINERJA KEUANGAN PADA LUAS UNGKAPAN TANGGUNG JAWAB SOSIAL PERUSAHAAN - Irawati, Eka (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
The purpose of this research is to analyze the influence of companyâs financial performance to the disclosurerange of Corporate Social Responsibility. the disclosure range of Corporate Social Responsibility is proxy byCorporate Social Disclosure Index (CSRI) while financial performance is proxy by Return on Assets (ROA),Return on Equity (ROE), and Debt to Equity Ratio (DER). The samples are banking companies which are listedin Indonesia Stock Exchange. The samples are 28 companies which have been selected by using purposivesampling method. The multiple linear regressions analysis is used as statistics method. The result shows thatfinancial performance (return on asset, return on equity, and debt to equity ratio) does not influence thedisclosure range of Corporate Social Responsibility. It is assumed that since there is a possibility that thecompany retain profit for asset development, it shares their profit to the shareholders, and the company limitstheir expenses, so the disclosure of Corporate Social Responsibility is not as wide as it has been expected.Keywords: Return on Assets, Return on Equity, Debt to Equity Ratio, and Disclosure Range of CorporateSocial Responsibility.